Interactions among Low Dose of Methotrexate and Drugs Used in the Treatment of Rheumatoid Arthritis - Marinella Patanè; Miriam Ciriaco; Serafina Chimirri; Francesco Ursini; Saverio Naty; Rosa Daniela Grembiale; Luca Gallelli; Giovambattista De Sarro; Emilio Russo (Hindawi Limited, 2013)
Methotrexate (MTX) is a nonbiological disease-modifying antirheumatic drug that has shown both a good control of clinical disease and a good safety. Usually drug-drug interactions (DDIs) represent the most limiting factor during the clinical management of any disease, in particular when several drugs are coadministered to treat the same disease. In this paper, we report the interactions among MTX and the other drugs commonly used in the management of rheumatoid arthritis. Using Medline, PubMed, Embase, Cochrane libraries, and Reference lists, we searched for the articles published until June 30, 2012, and we reported the most common DDIs between MTX and antirheumatic drugs. In particular, clinically relevant DDIs have been described during the treatment with MTX and NSAIDs, for example, diclofenac, indomethacin, or COX-2 inhibitors, and between MTX and prednisone or immunosuppressant drugs (e.g., leflunomide and cyclosporine). Finally, an increase in the risk of infections has been recorded during the combination treatment with MTX plus antitumor necrosis factor-α agents. In conclusion, during the treatment with MTX, DDIs play an important role in both the development of ADRs and therapeutic failure.